Developing the Competency Assessment Instrument for Learning Management During Covid 19 Period of the Student Teacher, Faculty of Education, SuanSunandha Rajabhat University - Eakwannang, Wipawan (Journal of Graduate MCU KhonKaen Campus, 2022)
An objective of this research is to developing the competency assessment instrument for learning management during COVID 19 period of the student teacher, Faculty of Education, Suan Sunandha Rajabhat University which conform to the bachelor degree’s qualification standard for Education Department (4 years course), 2019. The research populations are the 3 academies whom approve the tool and the 139 second-year students whom study in the childhood education and social science teaching. The tool that used for approving the content validity quality is the compatible evaluation form between the list of learning management evaluation during COVID 19 period by the online teaching and the process of learning management. The tool that used for approving the reliability of instrument is trailed to the 35 students whom study the learning’s science management subject (English in the course of Instructional Science). The results found that the development of competency assessment instrument for learning management during COVID 19 period of the student teacher, Faculty of Education, Suan Sunandha Rajabhat University which conform to the bachelor degree’s qualification standard for Education Department (4 years course), 2019 consist of 4 major measurement items viz 1) the writing of learning management plan which is composed of 5 measurement items 2) the preparation of objects used for the learning management which is composed of 6 measurement items 3) the learning management which is composed of 30 measurement items and 4) the recording after the learning management which is composed of 5 measurement items. The results of approving the tool quality on the content validity reveal that the IOC values of 41 measurement items are 1.00 and 4 measurement items are 0.67. The result of reliability analysis by Cronbach’s alpha is equal value of .912